Social Media Ethics for Women to Reduce Cyber Crime (Holistic Thematic Qur'an Tafsir Study) - Syakira, S; Nugoho, Kharis (Universitas Muhammadiyah Surakarta, 2023)
The increasingly widespread use of social media in the digital era has given rise to new challenges related to cyber security, including an increase in cyber crime incidents involving women. This study discusses social media ethics for women to reduce cyber crime, with a holistic thematic interpretation approach. This research proposes to focus on the role of women in maintaining social media ethics to reduce the impact of cyber crime. This study outlines the global context of social media use, with a special emphasis on the role of women in mitigating cyber threats. Through a qualitative approach that uses a holistic thematic interpretation method, this study also explores women's perspectives related to social media ethics, responses to cyber threats, and strategies used to protect themselves and their families. This research is expected to provide in-depth insights into the role of women in shaping a safer and ethical online environment. The practical implications of this study involve the preparation of a special social media ethics guide for women, strengthening awareness about cyber risks, and active involvement of women in cyber security advocacy. By combining ethical and gender dimensions in the context of social media, this research seeks to make a positive contribution to our understanding of how women can play the role of agents of change in facing the complex challenges faced by today's digital society.